2016
DOI: 10.1107/s2053229616008925
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structures of tris(1-tert-butyl-2-mercaptoimidazolyl)hydroborate complexes of titanium, zirconium and hafnium

Abstract: Cyclopentadienyl and tris(pyrazolyl)hydroborate have found much use as supporting ligands in the chemistry of titanium, zirconium and hafnium, especially with respect to applications involving olefin polymerization catalysis. In contrast, closely related tris(1-alkyl-2-mercaptoimidazolyl)hydroborate, [Tm], ligands have so far found little application to the chemistry of these elements, despite the fact that such ligands are currently used extensively in coordination chemistry. In view of the fact that a substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The fact that the methylene groups appear as a singlet is, nevertheless, rationalized by facile enantiomer interconversion due to propeller inversion of the [To RBenz ] ligand, as noted above for Cp­[To MeBenz ]­ZrCl 2 . In this regard, it is pertinent to note that the methylene hydrogen atoms of the mercaptoimidazolyl counterpart [Tm Bu t ]­Zr­(CH 2 Ph) 3 appear as two doublets in the 1 H NMR spectrum . As such, the result is in accord with the spectral differences noted above for Cp­[To MeBenz ]­ZrCl 2 and Cp­[Tm Me ]­ZrCl 2 , which also indicate that the oxoimidazolyl system is more flexible than the sulfur counterpart.…”
Section: Results and Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The fact that the methylene groups appear as a singlet is, nevertheless, rationalized by facile enantiomer interconversion due to propeller inversion of the [To RBenz ] ligand, as noted above for Cp­[To MeBenz ]­ZrCl 2 . In this regard, it is pertinent to note that the methylene hydrogen atoms of the mercaptoimidazolyl counterpart [Tm Bu t ]­Zr­(CH 2 Ph) 3 appear as two doublets in the 1 H NMR spectrum . As such, the result is in accord with the spectral differences noted above for Cp­[To MeBenz ]­ZrCl 2 and Cp­[Tm Me ]­ZrCl 2 , which also indicate that the oxoimidazolyl system is more flexible than the sulfur counterpart.…”
Section: Results and Discussionsupporting
confidence: 68%
“…For example, we previously reported that thallium compounds of the type [Tp R,R′ ]Tl are effective reagents for the synthesis of [Tp R,R′ ]­MR x –1 derivatives (e.g., M = Mg, Zn, Al) via reactions with MR x , , because decomposition of the incipient TlR byproduct provides an effective driving force for the reaction . Accordingly, the benzyl compounds [To R ]­Zr­(CH 2 Ph) 3 may be conveniently obtained by the metathesis of Zr­(CH 2 Ph) 4 with the corresponding thallium reagent [To R ]Tl (Scheme ), an approach that has also been employed for [Tm Bu t ]­M­(CH 2 Ph) 3 (M = Zr, Hf) and [Tp Ms* ]­Hf­(CH 2 Ph) 3 . , …”
Section: Results and Discussionmentioning
confidence: 99%